CCAAT/Enhancer-binding Protein α (C/EBPα) and Hepatocyte Nuclear Factor 4α (HNF4α) Synergistically Cooperate with Constitutive Androstane Receptor to Transactivate the Human Cytochrome P450 2B6 (CYP2B6) Gene: APPLICATION TO THE DEVELOPMENT OF A METABOLICALLY COMPETENT HUMAN HEPATIC CELL MODEL - Benet, Marta (American Society for Biochemistry and Molecular Biology, 2010)
The transcription of tissue-specific and inducible genes is usually subject to the dynamic control of multiple activators. Dedifferentiated hepatic cell lines lose the expression of tissue-specific activators and many characteristic hepatic genes, such as drug-metabolizing cytochrome P450. Here we demonstrate that by combining adenoviral vectors for CCAAT/enhancer-binding protein α (C/EBPα), hepatocyte nuclear factor 4α (HNF4α), and constitutive androstane receptor, the CYP2B6 expression and inducibility by CITCO are restored in human hepatoma HepG2 cells at levels similar to those in cultured human hepatocytes. Moreover, several other phase I and II genes are simultaneously activated, which suggests that this is an effective approach to endow dedifferentiated human hepatoma cells with a particular metabolic competence and response to inducers. In order to gain insight into the molecular mechanism, we examined the cooperation of these three transcription factors on the CYP2B6 5′-flanking region. We show new CYP2B6-responsive sequences for C/EBPα and HNF4α and a novel synergistic regulatory mechanism whereby C/EBPα, HNF4α, and constitutive androstane receptor bind and cooperate through proximal and distal response elements to confer a maximal level of expression. The results obtained from human liver also suggest that important differences in the expression and binding of C/EBPα and HNF4α could account for the large interindividual variability of the hepatic CYP2B6 enzyme, which metabolizes commonly used drugs.